A CASE STUDY OF INTERNAL AND EXTERNAL FACTORS ON THE DIFFICULTIES IN LEARNING ENGLISH - Wulandari, Cahya; Surtikanti, Monika Widyastuti; Agung, Antonius Setyawan Sugeng Nur (English Language Education Study Program, 2020)
Difficulties in Learning English in EFL context are always interesting. Analysing it from the view of external and internal factors is the major interest of this case study. Describing the findings qualitatively is the purpose of this study. The subject in this research was the eleventh graders at SMAN 2 Sengah Temila in Landak Regency. There were 76 students participated in this study. The sources of the data were gathered from the classroom teacher, the students, and the portfolios. Data collection techniques in this research were: open-ended questionnaire, in-depth interview, and observation. Meanwhile, data analysis techniques used interactive analysis.This study finds the internal and the external factors affect the learning difficulties. The indicators on internal factors show (a) health conditions has no significant effect on learning difficulty, (b) the students interest and motivation affect the learning difficulty because no variation on the teaching method bored the students, (c) bad habits in studying evoke the learning difficulties. The indicators on external factors find (a) the teacher has a significant role to expand learning difficulties especially on the use of teaching method and media, (b) the classroom environment has no significant effect in learning difficulties since it is a conservative one.